(untitled) (Annals of Medical Research, 2019)
Aim: In this study, we aimed to find out the positive and negative effects of the pregraduation anatomy education received by academic staff working in the Faculty of Dentistry on their professions both as an educator and as a dentist. Material and Methods: The study was conducted through a questionnaire given to 19 academic staff at Uşak University Faculty of Dentistry. A 5-Likert type scale was used for the reliability of feedback.Results: Of the academic staff who participated in the study, 3 were research assistants, 13 were assistant professors, 1 was associate professor and 2 were professors. 84% of the academic staff who participated in the study stated that they “liked the anatomy course during their undergraduate education” and 95% stated that “the content of anatomy course was useful in professional sense”. 90% of the participants stated that “there should be an anatomy department in dentistry faculties”. Conclusion: We believe that these feedbacks we get from the academic staff participants will contribute to anatomy education given during undergraduate period in dentistry education.